Painting biological low-frequency vibrational modes from small peptides to proteins1. Issue 17 (7th May 2015) - Perticaroli, S.; Russo, D.; Paolantoni, M.; Gonzalez, M. A.; Sassi, P.; Nickels, J. D.; Ehlers, G.; Comez, L.; Pellegrini, E.; Fioretto, D.; Morresi, A.
<x xml:space="preserve">Abstract</x> We use experiments and simulation to investigate the validity of different model systems used to study the low-frequency vibrations of proteins.